ИСПОЛЬЗОВАНИЕ СВОЙСТВ ФУНКЦИЙ ДЛЯ ОЦЕНКИ ЗНАЧЕНИЙ ВЫРАЖЕНИЙ (Scientific journal of the Fergana State University, 2023)
In this paper the methods of using function’s properties for solution of some examples are given.